2004
DOI: 10.1634/stemcells.22-6-972
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Fibroblast‐Like Cells Derived from Human Embryonic Stem Cells Support Undifferentiated Cell Growth

Abstract: Human embryonic stem cells (hESCs) have the potential to generate multiple cell types and hold promise for future therapeutic applications. Although undifferentiated hESCs can proliferate indefinitely, hESC derivatives significantly downregulate telomerase and have limited replication potential. In this study we examine whether the replicative lifespan of hESC derivatives can be extended by ectopic expression of human telomerase reverse transcriptase (hTERT), the catalytic component of the telomerase complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
8

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 49 publications
(72 reference statements)
5
119
0
8
Order By: Relevance
“…Although the generation of fibroblast-looking cells from human ESCs was originally reported a few years ago, those cells were not fully characterized as MSCs [23][24][25]. Barberi et al were the first to derive MSCs from human ESCs through co-culturing them with the OP9 murine BM stromal cell line for 40 days and characterize them according to accepted criteria for MSCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although the generation of fibroblast-looking cells from human ESCs was originally reported a few years ago, those cells were not fully characterized as MSCs [23][24][25]. Barberi et al were the first to derive MSCs from human ESCs through co-culturing them with the OP9 murine BM stromal cell line for 40 days and characterize them according to accepted criteria for MSCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts at producing functional cartilage from human embryonic cell derivatives under chondrogenic conditions have not always been successful, although these cells readily undergo osteogenic and adipogenic differentiations in standard culture conditions [13,40]. Our tailored coculture system, on the other hand, has enabled LVEC cells to undergo chondrogenic differentiation to produce a tissue with a morphology indicative of hyaline cartilage in a 3D environment.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast-like cells have been derived from H1 cells (WA01), denoted HEF1, and immortalized by infection with a retrovirus expressing human telomerase reverse transcriptase (TERT) (Xu et al, 2004). It was found that conditioned medium from these cells supported the growth of both H7 and H9 cells (WA07 and WA09) on Matrigel.…”
Section: Conditioned Mediummentioning
confidence: 99%